The Practice of Buying and Selling Artificial Insemination Seeds in Cows Reviewed According to Sharia Economic Law - Akmaluddin.MS; M, Nur Sari Dewi; Putri, Juliana; Mulyani, Rita (Syarah: Jurnal Hukum Islam dan Ekonomi, 2024)
The local cattle crossbreeding program with exotic cattle was developed as a result of the high demand from farmers for artificial insemination of exotic cattle. The number of local cattle is expected to decline over time and may be threatened with extinction. These artificial inseminations have been distributed through ordering, direct sales and distribution systems. The problems are (1) How is the mechanism of the sale and purchase transaction of artificial insemination seeds in cattle carried out in sharia? (2) What is the view of Sharia Economic Law on the practice of buying and selling artificial insemination seeds in cattle? The type of this research is qualitative with a field approach (Field Research), the data collection methods used are observation, interview, and documentation methods. The results of this study are (1) The mechanism of the practice of buying and selling artificial insemination seeds in cattle has been running in sharia is known to use tabarru` contracts based on service turnover, namely the wakalah contract that the mechanism of buying and selling artificial insemination practices only focuses on operational payments for orderlies' services in helping and helping farmers. (2) The view of sharia economic law on the practice of buying and selling artificial insemination seeds in cows using a tabarru` contract based on the replacement of the services of the wakalah contract which contains elements of help, so that this buying and selling practice is permissible according to the principles of sharia economic law, namely the benefit of hajjiyah.